Occupational Health and Safety Risk Analysis Using AS/NZS Standard 4360:2004 in a Fish Meatball Industry - Dewi, Resti Nurmala (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2023)
The Indonesian fishing industry developed by 1.4% in 2020, compared to the previous year, as shown by the existence of around 773 seafood factories. Such growth caused the emergence of different working conditions due to the use of complex machines. In 2019, the industrialization process generated an immense potential for accidents on occupational health as the mishaps increased from 60 to 270 cases. For this reason, this study aimed to identify the value and level of risk, using HIRARC (Hazard Identification Risk Assessment and Risk Control) following AS/NZS 4360:2004 standards. The study was conducted at the fish meatball company located in East Java, for six months. The results showed that the company could manage the occupational health and safety, as indicated by the reduction of the levels of risk from acceptable (33.4%), priority 3 (14.3%), priority 2 risk (38.1%), priority 1 risk (9.5%), and very high risk (4.8%) to acceptable (76%) and priority 3 (24%). The risk assessment matrix had shifted from yellow (moderate) to green (low). Some recommendations implemented in the workplace included creating a safety organization, organizing training sessions among employees, fostering a safety culture, applying ergonomic principles, and controlling work hours.